Keywords Search Correction Using Damerau Levenshtein Distance Algorithm - Oktaviyani, Enny Dwi; Christina, Sherly; Ronaldo, Deddy (SENATIK STT Adisutjipto, 2019)
Searching is one of the important features on the website, but it is not uncommon for users to make typos when typing keywords. Typing errors of these keywords is usually referred to as typo. This study aims to build a system by providing suggestions for correcting typos in the search feature. Keywords search correction are obtained using the Damerau-Levenshtein Distance Approximate String Matching algorithm by to calculate the editing distance of each word in a keywords with each word in the Indonesian word dictionary. Testing was carried out as many as 40 experiments, with 10 keywords and 250 articles taken randomly. The test results show the Damerau-Levenshtein Distance algorithm is able to provide precision and recall values of 91.24% and 89.58% in providing keyword improvement suggestions. With the improvement of the system, each trial increases with precision value of 0.80 and recall value of 0.98